Are [6+4] Cycloadditions onto Graphene Possible?. Issue 29 (18th October 2017) - Denis, Pablo A.
Abstract: Herein, we have studied the feasibility of [6+4] cycloadditions onto graphene by means of first principle calculations. In the case of perfect graphene we were unable to find a stable cycloaddition product when tropone was used as 6 π electron system. However, the reaction with tropone can be attained when the graphene sheet is modified by the presence of functional groups such as hydrogen atoms or epoxy groups. In the same line, dopants were found to favor the accomplishment of [6+4] cycloadditions. In the best scenario, for heavily hydrogenated sheets or Si doped graphene, the reactions were highly exergonic, proceed without barrier and were preferred over the [4+2] path. With regards to edges, for saturated armchair edges the reaction was endergonic but possible since a stable [6+4] cycloaddition product could be found whereas for bare armchair edges the reaction proceeds smoothly. We propose that [6+4] cycloadditions can be used as a new approach towards the selective functionalization of graphene. Abstract : Theoretical calculations show that higher order cycloaddition reactions are possible onto doped graphene, graphene oxide, armchair edges and single sided hydrogenated/fluorinated graphene. In particular we found that the [6+4] cycloaddition of tropone is possible on the aforementioned graphene derivatives.